Analisa Motivasi dan Kinerja Penerapan Sistem Izin Kerja Aman pada Proyek Pembangunan Fasilitas Produksi Gas Alas Dara Kemuning di Pertamina EP Cepu ADK - Sanditya Agung Pratama; Bernard Hasibuan; Soehatman Ramli (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study was evaluated to assess the level of motivation and performance of the Safe Work Permit System (SIKA) implementation on the PT Pertamina EP Cepu ADK gas production facility construction project. The results showed that the level of motivation and performance of the implementation of SIKA at PT PDC was rated high by most respondents, but its implementation still faces challenges. Analysis using the Partial Least Square Structural Equation Model (PLS-SEM) method shows that the positive and significant influence of leadership style and infrastructure conditions on the motivation for implementing SIKA. However, leadership style does not have a significant influence on the performance of SIKA implementation, while infrastructure facilities make a positive and significant contribution to performance. The relationship between infrastructure facilities and IFS implementation performance is significantly mediated by the motivation to implement IFS, but not the relationship between leadership style and IFS implementation performance. The results of the study provide important insights for the management of PT PDC to further strengthen employee motivation, especially through the improvement of supporting infrastructure, in order to improve the performance and implementation of IAS. Although leadership style is rated high, the findings show that other factors such as infrastructure also play a role in improving the performance of SIKA implementation. In this context, management can focus more efforts on optimizing infrastructure to create a safe work environment and improve the implementation of SIKA. This finding has high relevance for other oil and gas industry companies, especially in efforts to reduce the risk of work accidents.